2019
DOI: 10.1369/0022155419852932
|View full text |Cite
|
Sign up to set email alerts
|

Renal Inflammation and Fibrosis: A Double-edged Sword

Abstract: Renal tissue injury initiates inflammatory and fibrotic processes that occur to promote regeneration and repair. After renal injury, damaged tissue releases cytokines and chemokines, which stimulate activation and infiltration of inflammatory cells to the kidney. Normal tissue repair processes occur simultaneously with activation of myofibroblasts, collagen deposition, and wound healing responses; however, prolonged activation of pro-inflammatory and pro-fibrotic cell types causes excess extracellular matrix d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
88
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(93 citation statements)
references
References 202 publications
(284 reference statements)
0
88
0
5
Order By: Relevance
“…A similar trend was also observed in the expression of the ltbp1 gene which encodes for the LTBP1 protein, involved in the activation of TGFβ-1. Of note, these data suggest a possible mechanism of action of MSC-EVs in the regulation of TGFβ-1, which itself is a key stone in the progression of inflammation and fibrosis (Wang et al, 2008;Black et al, 2019). miRNAs are non-coding RNA molecules, that function as post-transcriptional regulators, blocking target mRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar trend was also observed in the expression of the ltbp1 gene which encodes for the LTBP1 protein, involved in the activation of TGFβ-1. Of note, these data suggest a possible mechanism of action of MSC-EVs in the regulation of TGFβ-1, which itself is a key stone in the progression of inflammation and fibrosis (Wang et al, 2008;Black et al, 2019). miRNAs are non-coding RNA molecules, that function as post-transcriptional regulators, blocking target mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of inflammatory, fibrotic, and reparative processes occur simultaneously to promote regeneration and repair, following an insult. An increase in the infiltration of inflammatory and pro-fibrotic cells can impair tissue regeneration and lead to fibrosis (Black et al, 2019). Renal fibrosis characterised by progressive tissue scarring is a hallmark of CKD and a prominent feature of AAN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of proinflammatory cytokines/chemokines is a key initiating step in renal fibrogenesis. 26 Therefore, we examined the expression of some proinflammatory cytokines/chemokines, including MCP-1, RANTES, TNF-α, and IL-1β, in the kidney by enzyme-linked immunosorbent assay (ELISA). The results showed that the levels of these molecules were significantly increased in the kidney of HN rats.…”
Section: Ppar-γ Activation Inhibits the Release Of Cytokines/chemokinmentioning
confidence: 99%
“… 23 Chronic fibrotic conditions in dermal, lung, liver, and kidney tissue are also characterized by myofibroblast persistence. 24 , 25 , 26 , 27 Thus, targeting myofibroblasts is a goal of fibrotic therapies, and the transparent cornea is an interesting and accessible model system for testing even non-ocular anti-fibrotic therapies. 20 …”
Section: Introductionmentioning
confidence: 99%